Perencanaan Keseimbangan Air pada Embung Bratayudha - Siti Yuni Yuningsih; Sulwan Permana (Institut Teknologi Garut, 2025)
Water balance in the planning of Embung Bratayudha is one of the efforts to control flooding when runoff or high water discharge in the rainy season and to meet the needs of the community for the availability of raw water for irrigation. Based on this, research is needed to analyze the water balance planning at Bratayudha Embung, so that the needs and availability of water in the embung will be known. The method used in this research is a quantitative approach by analyzing primary data obtained through field surveys and secondary data obtained from Kepakan Station Post and the Garut Regency Public Works and Spatial Planning Office.The results of the NRECA analysis conducted can be known water availability discharge of 0.3014 m³/s where this discharge is obtained from the mainstay discharge with a probability of 80%, and the water demand discharge of 0.28 m³/s. From the analysis of the K factor that compares the discharge of availability and needs, the amount of 1.048 m³/s is obtained, where if the value of K â‰¥ 1 then the availability of water can be fulfilled, so the water balance of the reservoir is balanced.